2016
DOI: 10.1371/journal.pone.0149174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Structure of Surgical Activity for a Suturing and Knot-Tying Task

Abstract: BackgroundSurgical tasks are performed in a sequence of steps, and technical skill evaluation includes assessing task flow efficiency. Our objective was to describe differences in task flow for expert and novice surgeons for a basic surgical task.MethodsWe used a hierarchical semantic vocabulary to decompose and annotate maneuvers and gestures for 135 instances of a surgeon’s knot performed by 18 surgeons. We compared counts of maneuvers and gestures, and analyzed task flow by skill level.ResultsExperts used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…This shows that the described techniques perform 8× to 10× better than chance, (2) for the case of joint segmentation and classification, the granularity of the classifier is very fine at frame level which is about 0.03 second long, and (3) at this granularity, independent human annotators agree only on 75% to 80% of the frames [26], [27]. Therefore for a machine (trained to replicate manual labels) a performance of 80% is within the range of human labeling performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the described techniques perform 8× to 10× better than chance, (2) for the case of joint segmentation and classification, the granularity of the classifier is very fine at frame level which is about 0.03 second long, and (3) at this granularity, independent human annotators agree only on 75% to 80% of the frames [26], [27]. Therefore for a machine (trained to replicate manual labels) a performance of 80% is within the range of human labeling performance.…”
Section: Resultsmentioning
confidence: 99%
“…In this approach, fine-grained segmentation and labeling are thus necessary steps for surgical skill assessment. Recent studies [26]–[28] have shown that given the sequence of surgical gestures and their boundaries, one can predict the surgeon’s skill level with up to 90% accuracy for new trails of known (observed) surgeons or 75% accuracy for a new trails of unobserved surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…One of the fundamental tasks in the development of this surgical automation framework was the hierarchical decomposition of surgical motion patterns. The workflow of surgical interventions, as well as the motion of the surgeon, can be decomposed into elements on different levels of granularity [29][30][31], similar to behavior trees [32]. In the literature, there are several different definitions of some granularity levels, nevertheless, no consistent definition can be found for the whole domain.…”
Section: Methodsmentioning
confidence: 99%
“…A suture operation can be broken down into detailed steps. There is an excellent study on the analysis of a suturing and knot-tying task [13]. This work adopted for the design and implementation of the suturing simulation.…”
Section: Running Subcuticular Suturesmentioning
confidence: 99%